Perceived value and barriers of nursing specialty certifications among clinical nurses in Saudi Arabia: a cross-sectional study - AlSadah, Alawiah T.; Aboshaiqah, Ahmad E.; Alanazi, Naif H. (Frontiers in Medicine, 2025)
IntroductionSpecialty nursing certifications reflect nurse’s knowledge and competence in certain areas. Obtaining certification allows them to advance their careers and enhance patient care standards as their role and scope of responsibility expands. This study aimed to understand how nurses view specialty certification and related challenges in three university hospitals in Riyadh, Saudi Arabia.MethodsA cross-sectional, correlational design was used. A survey questionnaire (Perceived Value of Certification-12 Tool) was sent through email, and it had one question for each barrier.ResultsThe majority of participants valued certification to verify specialist knowledge (93.9%), enhance achievement (82.8%), and increase competence (79.1%). Certification was associated extrinsically with hiring preference (54.7%), recognition from colleagues (52.3%), and professional autonomy (51.7%). The primary barriers were lack of institutional reward (72.7%) and examination cost (64.8%), with not passing earlier being the least mentioned barrier (2%). The biggest obstacles faced by clinical nurses in obtaining certification include limited institutional rewards because their organization did offer incentives, such as promotions or salary bumps. Age and hospital significantly predicted clinical nurses’ intrinsic value of certification, while age, gender, nationality, and hospital significantly predicted their extrinsic value. Age and gender significantly influenced their overall perceived value of certification.DiscussionOverall, nurses in Riyadh recognize the value of certification. However, focused interventions must be implemented to overcome identified challenges and amplify the professional benefits of certification. Recommended measures include implementing tailored support initiatives and financial aid programs to address these barriers. A collaborative approach should be developed to provide support and actively promote the pursuit of nursing certification. Future studies should adopt longitudinal and qualitative designs to evaluate the impact of focused strategies.